Effect of immunonutrition during concurrent chemoradiotherapy on acute oral mucositis in head and neck cancer patients: A prospective randomized study. - Pooriwat Muangwong; Tharatorn Tungkasamit; Vatanyu Samakgarn; Ausareeya Chumachote; Kittikun Kittidachanan; Imjai Chitapanarux (PLoS ONE)
Objective Immunonutrition (IN) supplements, designed to modulate immune system, may help reduce treatment-related toxicities. This study aimed to evaluate the efficacy of IN in reducing acute oral mucositis (OM) and other side effects in head and neck cancer patients undergoing concurrent chemoradiotherapy (CCRT). Methods A multicenter, prospective, open-label randomized controlled study was conducted to assess the impact of IN on reducing OM and other side effects in head and neck cancer patients undergoing CCRT. Patients were randomized into either IN or control arms. Those in the IN arm received IN sachets starting one week before radiotherapy until treatment completion, while the control arm received no supplement. Treatment outcomes were evaluated using Common Terminology Criteria for Adverse Events (CTCAE) version 5 and patient-reported outcomes via National Cancer Institute's Patient-Reported Outcomes of CTCAE (NCI-PRO-CTCAE). Mixed-effects logistic regression was performed to analyze outcomes between the groups, adjusting for chemotherapy regimens, while Chi-squared tests were used for group comparisons at specific timepoints. Results A total of 87 patients were analyzed with 46 in IN arm and 41 in control arm. Physician evaluations showed similar rates of grade 2 or higher OM, dermatitis, esophagitis, and hematologic toxicities across both arms. Patient-reported outcomes also showed no significant differences in the severity of oral mucositis or its interference with daily activities. A significant reduction of dermatitis was observed at week 3 in the IN arm (9.8% vs. 34.8%, p =  0.03), but this effect was not sustained in later weeks. Conclusion IN supplementation during CCRT did not result in statistically significant reductions in acute oral mucositis and other radiation toxicities. Further research with larger sample sizes, compliance monitoring, and optimized supplementation protocols is warranted to better understand the potential benefits of IN.